(untitled) (Revista de Ciências Agroveterinárias, 2006)
The scarcity of natural resources, in addition to the increasing concern about the environment, is forcing man kind to develop energy alternatives from renewable and biodegradable sources of a sustainable nature. In the search for such alternatives for motors with ignition by compression, biodiesel rises as a biofuel option derived from the reaction of plant oils with anhydrous alcohol. The objective of the present study was to compare the fuel consumption of an agricultural tractor functioning of alternate form with filtered and distilled biodiesel in a direct planting operation. A factorial scheme with fully randomized blocks was used as experimental design, combining seven mixture proportions (B0, B5, B15, B25, B50, B75 and B100) and two types of biodiesel (filtered and distilled). Hourly consumption as a volume unit (L h-1) and mass (kg h-1) and specific consumption (g kWh-1) were determined. The results showed no difference in the specific consumption when the tractor used filtered or distilled biodiesel.